2023
DOI: 10.3390/su15065346
|View full text |Cite
|
Sign up to set email alerts
|

Secure and Lightweight Authentication Protocol for Privacy Preserving Communications in Smart City Applications

Abstract: A smart city is a concept that leverages technology to improve the quality of life for citizens, enhance sustainability, and streamline urban services. The goal of a smart city is to use data and technology to manage resources and assets efficiently, make informed decisions, and create a more livable and thriving city for its residents. Smart cities rely on a range of technologies including the Internet of Things (IoT), Artificial Intelligence (AI), big data analytics, and cloud computing to gather, process, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Gupta et al [8] identified drawbacks in an identity-based protocol used for remote working. They identified impersonation and insider attacks as the major loopholes.…”
Section: Literature Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…Gupta et al [8] identified drawbacks in an identity-based protocol used for remote working. They identified impersonation and insider attacks as the major loopholes.…”
Section: Literature Surveymentioning
confidence: 99%
“…They identified impersonation and insider attacks as the major loopholes. After that, [8] presented an improved ECC-based authentication scheme for mobile devices. However, [8] shows that the plan is lightweight and robust.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…As explained in 1 , 2 , smart cities utilize data-driven technologies to boost sustainability, efficiency, quality of life of the citizens and streamline city services. In addition, the usage of smart city data and technologies facilitate efficient and optimized management of resources, urban services and assets, as well as aiding in making informed decisions 3 , 4 . The advancements in big data, cloud computing, Flying Ad-Hoc Networks (FANET), Wireless Sensor Networks (WSNs), Artificial Intelligence (AI), 5th generation mobile network (5G) and Internet of Things (IoT) have led to considerable traction towards smart cities 5 – 8 .…”
Section: Introductionmentioning
confidence: 99%
“…FL is now being used in the IoT, which has a particularly large and complex network. The cost of communication between various devices can be very high, making it necessary to find a solution to this problem [9][10][11]. Although Deep Neural Networks (DNNs) have achieved good performances in many real-world scenarios, their high computation and memory requirements make them unsuitable for wider applications on resource-limited devices [12].…”
Section: Introductionmentioning
confidence: 99%